Management of lead (Pb) waste post-closing of used battery smelter - Ridwan Fauzi; Rita Rita; Siti Masitoh (Jurnal Litbang Industri, 2022)
Lead heavy metal (Pb) contamination increases along with the community-managed waste processing of used lead batteries. People living in the vicinity of the lead smelter are at risk of exposure to lead which can have an impact on health. This study aims to identify the level of lead in the environment around post-closure used battery melting. The research used a quantitative descriptive method approach. Data collection was carried out by interview and sampling test. The test sample was taken purposive at two smelting locations, namely Cinangka Village and Jagabaya Village in Bogor Regency, Indonesia. The results showed that there was still lead exposure in the soil and in the plants around the smelting site. The high lead levels that have been found require measurable remediation action. This is to minimize the risks that can be caused to humans who are active around the used battery smelting site. In addition to having a negative impact in the form of lead exposure, lead smelting also provides economic benefits for workers in a smelter. Involving workers in collecting or sorting used batteries is an alternative after closing the smelting site. Meanwhile, smelting activities are only carried out by authorized smelters.